Peran Regulasi Securities Crowdfunding dalam Mendukung Kegiatan Usaha Mikro, Kecil, dan Menengah di Indonesia - Delpiero, Maichle; Setiawan, Axel James; Yuniar, Alvita; Ardhana, Pramuditya (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
According to Ministry of Investmentsâ€™ and the Indonesian Investment Coordinating Boardsâ€™ data, Small Micro and Medium Enterprises (â€œMSMEsâ€) have contributed Rp 8,574 trillion 61% of the value of Gross Domestic Product (â€œGDPâ€). Looking at the potential of MSMEs that can support the national economy, the Indonesian government has begun to shift its focus to empowering MSMEs. One of the root causes that hinder the efforts to scale up the MSMEs is about capital. This is exacerbated by the condition of the COVID-19 outbreak in 2020 that has reduced the possibility and opportunities for MSMEs to raise capital. Along with the recovery of MSMEs in Indonesia after COVID-19, the Indonesian government has provided diverse economic stimulus. One of them is by issuing Financial Services Authority Regulation Number 57/POJK.04/2020 of 2020 which essentially regulates Securities Crowdfunding (â€œSCFâ€). The regulation has been updated to accelerate the empowerment of MSMEs in Indonesia through the Financial Services Authority Regulation Number 16/POJK.04/2021 of 2021. This study uses normative juridical methods through a secondary data approach, aiming to break down and analyze how the financing model and implementation of SCF regulations will support MSMEs. This study has resulted that the role of SCF regulation has strategically supported MSME activities in Indonesia through various facilities.